Electron transfer between adjacent layers in self-assembled films - Leite, VBP; Ferreira, M.; Oliveira, O. N. (Elsevier B.V., 2000)
A simple model of electron transfer is adapted to explain fluorescence quenching in self-assembled films of poly( p-phenylene vinylene) (PPV) alternating with poly(thiophene acetic acid) (PTAA). Quenching is caused by a photo-induced electron transfer between the excited PPV (donor, D) and the PTAA (acceptor, A). The electron-transfer process can be mediated by insertion of electronically inert spacing bilayers between the D and A layers, As the number of bilayers is increased, the fluorescence is gradually recovered which is explained theoretically by assuming that the electron-transfer rate can be described as k = Z exp(- beta r) where r is the distance between D and A. (C) 2000 Elsevier B.V. B.V. All rights reserved.